Pillars of the Ganesha Mandapa having the Purnaghata Kalasha - Temples of India Project Team (Jio Institute, 2024)
The pillars of the Ganesha mandapa (pillared hall have a square base with purnaghata kalasha (vase and foliage motif), which is a symbol of prosperity and abundance. The middle part of the shaft is faceted and carved with standing female figures in varying states of preservation. At the top portion, each face of the shaft shows grassmukha (kirtimukha or face of glory), topped by a floral motif abacus. Above the abacus, brackets are placed to support the flat roof.